Absorption–Reflection–Transmission Power Coefficient Guiding Gradient Distribution of Magnetic MXene in Layered Composites for Electromagnetic Wave Absorption - Zhou, Yang; Zhang, Wen; Pan, Dong; Li, Zhaoyang; Zhou, Bing; Huang, Ming; Mi, Liwei; Liu, Chuntai; Feng, Yuezhan; Shen, Changyu (Nano-Micro Letters, 2025)
The morphological distribution of absorbent in composites is equally important with absorbents for the overall electromagnetic properties, but it is often ignored. Herein, a comprehensive consideration including electromagnetic component regulation, layered arrangement structure, and gradient concentration distribution was used to optimize impedance matching and enhance electromagnetic loss. On the microscale, the incorporation of magnetic Ni nanoparticles into MXene nanosheets (Ni@MXene) endows suitable intrinsic permittivity and permeability. On the macroscale, the layered arrangement of Ni@MXene increases the effective interaction area with electromagnetic waves, inducing multiple reflection/scattering effects. On this basis, according to the analysis of absorption, reflection, and transmission (A–R–T) power coefficients of layered composites, the gradient concentration distribution was constructed to realize the impedance matching at low-concentration surface layer, electromagnetic loss at middle concentration interlayer and microwave reflection at high-concentration bottom layer. Consequently, the layered gradient composite (LG5-10–15) achieves complete absorption coverage of X-band at thickness of 2.00–2.20 mm with RLmin of −68.67 dB at 9.85 GHz in 2.05 mm, which is 199.0%, 12.6%, and 50.6% higher than non-layered, layered and layered descending gradient composites, respectively. Therefore, this work confirms the importance of layered gradient structure in improving absorption performance and broadens the design of high-performance microwave absorption materials. Highlights: 1 The layered arrangement and gradient distribution of magnetic MXene are firstly combined to improve the electromagnetic wave (EMW) RLmin and broaden effective absorption bandwidth. 2 Absorption, reflection, and transmission (A–R–T) power coefficient analysis is firstly used to guide the gradient distribution, so as to realize EMW incidence at low-concentration surface, loss at middle concentration interlayer and reflection at high-concentration bottom. 3 The layered gradient composite (LG5-10-15) achieves complete absorption coverage of X-band at thickness of 2.00-2.20 mm with RLmin of -68.67 dB.